The Fire from Within: Multiorgan Failure with Bimodal Rhabdomyolysis from Exertional Heat Stroke. (7th February 2020) - Ubaldo, Onion Gerald V.; Quiwa, Khia; Rollan, Rohana Elise; Tripon, Edhel; Sebastian, Elizabeth
Abstract : Heat stroke (HS) is a condition characterized by a rise in core body temperature and central nervous system dysfunction. It is divided into two types: classical and exertional. Exertional heat stroke (EHS) is accompanied by organ failure. Liver injury, presenting only with a rise in liver enzymes, is common but in rare conditions, acute liver failure (ALF) may ensue, leading to a potentially lethal condition. Most cases of EHS-induced ALF are managed conservatively. However, liver transplantation is considered for cases refractory to supportive treatment. Identifying patients eligible for liver transplantation in the context of an EHS-induced ALF becomes a medical dilemma since the conventional prognostic criterion may be difficult to apply, and there is paucity of literature about these specific sets of individuals. Recently, extracorporeal liver support has been gaining popularity for patients with liver failure as a bridge to liver transplant. In this case report, we present a young Filipino athlete with symptoms and clinical course consistent with EHS that developed multiorgan failure, initially considered a candidate for liver transplant and total plasma exchange, but clinically improved with supportive management alone. This patient was also found to have bimodal rhabdomyolysis during the course of his hospital stay as manifested by the bimodal rise in his creatine kinase enzymes.